Chapter 23: Carrot Production in Florida - George J. Hochmuth; Donald N. Maynard; Charles S. Vavrina; William M. Stall; Kenneth L. Pernezny; Susan E. Webb (EDIS)
This document is HS722, Horticultural Sciences Department, UF/IFAS Extension. Published December 2005.